Advances in Pacific basin business, economics and finance. Vol. 12 - Lee, Cheng-Few; Yu, Min-Teh (Advances in Pacific basin business, economics and finance, 2024)
Advances in Pacific Basin Business, Economics and Finance (APBBEF) is a series designed to focus on interdisciplinary research in finance, economics, and management among Pacific Rim countries. All articles published are peer-reviewed and recommended by one editorial board member. Topics of interest include, but are not limited to, the following: 1. Policy and management on financial markets and financial institutions; 2. Options, futures, and other derivatives markets; 3. Corporate finance and investment decisions; 4. Insurance and risk management; 5. Accounting, auditing, and taxation; 6. Artificial intelligence and new technology in finance; 7. ESG and sustainability; 8. Income, employment, and education; 9. Monetary and foreign exchange policy; 10. Other economic policies among the Pacific Rim countries. APBBEF is indexed in ABI/INFORM, EconLit, EBSCO, ProQuest, ResearchGate, and Google Scholar. Manuscript submission: Please use an email attachment in Microsoft Word format or PDF to Dr. Min-Teh Yu (mtyu@nycu.edu.tw) or Dr. Cheng-Few Lee (cflee@business.rutgers.edu).